Children and ADRs (Adverse Drug Reactions) - Napoleone Ettore (BMC, 2010)
Abstract Many medicines are prescribed to the paediatric population on an unlicensed or 'off-label' basis because they have not been adequately tested and/or formulated and authorized for use in appropriate paediatric age groups. Regulatory authorities also need to remind health professionals about the importance of their contribution towards the process of paediatric pharmacovigilance thanks to their reporting of adverse drug reactions. The lack of reliable data in the paediatric population is associated with specific problems including: limited availability of safety data due to the lack of clinical trials in the paediatric population; under- or over-dosing in some age groups due to the lack of pharmacokinetics data or dose-finding studies; maturation, growth and development of the paediatric population susceptible to drug-induced growth and development disorders as well as to delayed ADRs not findable in adults. Pre-marketing trials are able to provide information about the benefits of drugs but do not manage to establish a safety profile. Spontaneous reporting of suspected ADRs become an important means to promote reasonable warning signs. Therefore some ADRs may be known in their qualitative aspect and quantitative aspect only after successful marketing and use in the population during a "normal" use. When the drug is used in clinical practice in large unselected populations, epidemiological post-marketing studies are useful as they find their major confirmation in recalling all the events that occur during monitoring, with estimates of incidence of ADRs that can not be obtained by spontaneous reports. In these studies a significant role can be played by the Family Pediatricians with the participation to active pharmacovigilance projects.